The Influence of Port Facilities on Cruise Tourist Satisfaction: Insights from Benoa Port Bali - Antara, I Ketut; Sulistyawati, Agung Sri (E-Journal of Tourism; Volume 11 Number 2 (September 2024)DO - 10.24922/eot.v11i2.124164, 2024)
The assessment of tourist satisfaction represents a crucial metric for evaluating the extent to which the facilities provided to cruise ship tourists align with their expectations. As a tourism facility, Benoa Port is obliged to provide services that are precise and of a high quality, which are well received by tourists. It is anticipated that the provision of exemplary service at Benoa Port will lead to an enhancement in tourist satisfaction, which, in turn, will result in an overall increase in satisfaction levels among cruise ship tourists. The objectives of this study are to identify the facilities provided and accessible to cruise ship passengers at the Benoa Port Cruise Terminal and to analyze the impact of available facilities at Benoa Port, Bali, on the satisfaction of cruise ship tourists. This research employs a quantitative approach, using data collection techniques such questionnaires and as in-depth interviews. The presentation of data analysis results can be done formally (in tables) or informally (in narrative form). Based on the research findings, facilities at Benoa Port include turnaround services, port basin dredging, terminal expansion, additional x-ray machines, and an MSME plaza within the terminal area. Data analysis concluded that Benoa Port facilities in Bali significantly influence cruise tourist satisfaction. With a t-value of 12.200 and a significance level of 0.000, the null hypothesis is accepted. The determination test shows that approximately 89.2% of the tourist satisfaction variable is influenced by port facilities.